2013
DOI: 10.1097/spv.0b013e31829c6365
|View full text |Cite
|
Sign up to set email alerts
|

Apical Descent in the Office and the Operating Room

Abstract: Objectives The support of the uterine cervix assessed in the clinic with Valsalva or cough and operating room (OR) with traction often differs. The objective of this study is to test the null hypothesis that the difference between preoperative and intraoperative values of POP-Q (Pelvic Organ Prolapse Quantification) point C is not related to prolapse size, and to determine if other factors exist that predict this difference. Methods This is a retrospective review of women who had a vaginal hysterectomy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
2
12
1
Order By: Relevance
“…In fact, uterine location at rest in the OR was equal to or lower than the maximal Valsalva location seen in MRI for 90 % (17/19) of women. Although this comparison has not been previously reported, Crosby et al reported that cervix location is, on average, 3.5 cm lower in the OR under traction vs POP-Q exam in clinic during maximal Valsalva [13]. We hypothesized that conditional differences between the OR and MRI environments may help explain some of these findings.…”
Section: Discussionmentioning
confidence: 76%
“…In fact, uterine location at rest in the OR was equal to or lower than the maximal Valsalva location seen in MRI for 90 % (17/19) of women. Although this comparison has not been previously reported, Crosby et al reported that cervix location is, on average, 3.5 cm lower in the OR under traction vs POP-Q exam in clinic during maximal Valsalva [13]. We hypothesized that conditional differences between the OR and MRI environments may help explain some of these findings.…”
Section: Discussionmentioning
confidence: 76%
“…Foon et al, 3 in their 3-month follow-up study, reported that "intraoperative cervical traction" with apical prolapse < À1 cm did not inform them of the need to perform concurrent vaginal hysterectomy at the time of anterior repair. However, Crosby et al 12 reported that a C point > 5 cm (a threshold at which they would intervene) was evident in 33% of 206 women studied in their series. Surprisingly, this difference was more evident in women with lesser degrees of prolapse: 70.3% (57/81) with stage 1 prolapse versus 9.3% (4/43) with stage 2 prolapse, and 8.5% (7/82) with for stage 3 prolapse (p < 0.001).…”
Section: Discussionmentioning
confidence: 94%
“…12 This phenomenon may be attributed to (1) dynamic changes in vaginal pressure forces accentuating areas of fascial tears in other compartments following repair of one compartment, or (2) unrecognized defects at the completion of the initial prolapse repair procedure. 13e15 Some recurrences are purely anatomical and tend to remain asymptomatic when mild or moderate.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,6 This difference may be partially explained by different environmental and loading conditions (i.e., Valsalva vs. traction, leg position, anesthesia, etc.) to which the apical ligaments are subjected.…”
Section: Introductionmentioning
confidence: 99%